2002
DOI: 10.1046/j.1341-8076.2002.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of 100 µg oral misoprostol every 3 hours and 6 hours for labor induction: A randomized controlled trial

Abstract: 100 microg oral misoprostol every 3 hours is more effective for labor induction than every 6 hours but there was no difference in mode of delivery, analgesic requirement, maternal complications and neonatal outcome. A dose of 100 microg misoprostol orally every 3 hours seems to be the optimum regimen and the new option for labor induction. However, further study should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Mean induction to delivery time was 20.5 h and similar to that reported by Thaisomboon [7,18,19,25]. Pongsatha et al reported that using a higher dose of oral misoprostol (100 mg every 3 or 6 h) dramatically decreased the induction to delivery interval (13.82 or 17.66 h depending on the regimen), with no difference on rates of women achieving vaginal birth within 24 h, but with an increase in side effects [24]. Rates of vaginal deliveries (75.7%) and delivery within 24 h of initiation of labor induction (65%) in our study are also similar to those reported in the literature, even if we take into account that two-thirds of included women had an initial BS 2 [7,18,19,23,25].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Mean induction to delivery time was 20.5 h and similar to that reported by Thaisomboon [7,18,19,25]. Pongsatha et al reported that using a higher dose of oral misoprostol (100 mg every 3 or 6 h) dramatically decreased the induction to delivery interval (13.82 or 17.66 h depending on the regimen), with no difference on rates of women achieving vaginal birth within 24 h, but with an increase in side effects [24]. Rates of vaginal deliveries (75.7%) and delivery within 24 h of initiation of labor induction (65%) in our study are also similar to those reported in the literature, even if we take into account that two-thirds of included women had an initial BS 2 [7,18,19,23,25].…”
Section: Discussionsupporting
confidence: 80%
“…This dosage falls into the category of low dosing (550 mg) which has demonstrated good efficacy and few side effects [10]. The mean dose of oral misoprostol needed for cervical ripening was 104 mg, corresponding to previous results ranging from 103 mg when using 50 mg/4 h to 272 mg when using 100 mg/3 h [24,25]. Mean induction to delivery time was 20.5 h and similar to that reported by Thaisomboon [7,18,19,25].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…But uterine hyperstimulation and abnormal fetal heart rate pattern occurred more commonly in the vaginal route. So oral misoprostol is safer and better accepted by pregnant women 30,31,32,33 .…”
Section: History and Backgroundmentioning
confidence: 99%